Synthesis and Characterization of Polyurethane Matrix Nano Composites - Anbazhagan, R.; Rajamani, G.P. (Asian Journal of Chemistry, 2014)
A gel-casting method was used to fabricate the polyurethane polymer matrix composites with commercially available molybdenum disulphide (5 to 20 wt. %) and nano particles of titanium dioxide (0.5 to 2 wt. %) were added to tetrahydrofuran. Polyurethane was added pellet wise to stirred suspension. To maintain feasible viscosity of the suspension, the concentration of the polyurethane had to be reduced in the solution. Variation was made in the concentration of polyurethane in tetrahydrofuran from 3.5 to 10 wt. %, the suspension was being continuously stirred for 1 h to ensure the complete dissolution of the pellets of polyurethane. The suspension was then cast into different specimen sizes and was characterized through transmission electron microscopy, scanning electron microscopy and powder X-ray diffraction for morphological properties. The mechanical strength properties were determined by impact test, fracture test, wear and the friction test.